1997
DOI: 10.1046/j.1365-2311.1997.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of prey in the diet of the phytophagous thrips, Frankliniella schultzei

Abstract: 1. Patterns of mite egg consumption by the phytophagous thrips Frankliniella schultzei Trybom were investigated. Although F. schultzei predation is somewhat similar to that of F. occidentalis (Pergande), the understanding of predation by these two phytophagous thrips was extended, allowing the functional significance of flower thrips’ predatory behaviour to be reinterpreted.2. Second‐instar larvae consumed significantly more eggs than any other life‐stage, and the daily intake of eggs by second‐instar larvae d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…Frankliniella schultzei and Thrips tabaci are both phytophagous species, but both of them also function as predators, particularly against the eggs of mites (Milne & Walter 1997, 1998b. Frankliniella schultzei can cause marked feeding damage to cotton seedlings, but if the crop is not sprayed at this stage, this thrips subsequently becomes an effective predator of the far more harmful two-spotted spider mites (Wilson et al 1996), and growth by the cotton plants quickly compensates for the early season thrips damage.…”
Section: Immigrant and Pest Thripsmentioning
confidence: 99%
“…Frankliniella schultzei and Thrips tabaci are both phytophagous species, but both of them also function as predators, particularly against the eggs of mites (Milne & Walter 1997, 1998b. Frankliniella schultzei can cause marked feeding damage to cotton seedlings, but if the crop is not sprayed at this stage, this thrips subsequently becomes an effective predator of the far more harmful two-spotted spider mites (Wilson et al 1996), and growth by the cotton plants quickly compensates for the early season thrips damage.…”
Section: Immigrant and Pest Thripsmentioning
confidence: 99%
“…For example, Isenhour and Yeargan (1981) reported that adult females of Orius insidiosus Say (Heteroptera: Anthocoridae) killed more soybean thrips, Sericothrips variabilis Beach (Thysanoptera: Thripidae), than adult males. Milne and Walter (1997) reported that second-instar larvae of Frankliniella schultzei Trybom (Thysanoptera: Thripidae) devoured significantly more eggs than any other life stage. McConnell and Kring (1990) observed significant differences between the number of nymphs and adult aphids consumed by Coccinella septempunctata L. (Coleoptera: Coccinellidae).…”
Section: Discussionmentioning
confidence: 99%
“…Frankliniella occidentalis, F. schultzei y Thrips tabaci son consideradas plagas en todos los continentes (Mound 1997), presentan hábitos antófilos, folívoros y eventualmente se comportan como depredadoras (Lewis 1973, Trichilo & Leigh 1986, Van Rijn et al 1995, Wilson et al 1996, Milne & Walter 1997, 1998, Morse & Hoddle 2006. La situación de F. australis y F. gemina es diferente, ambas tienen distribución neotropical (Ortíz 1997, De Santis et al 1980, González 1999, Cavalleri et al 2006) y son de hábitos antófilos sobre una amplia variedad de plantas hospedadoras (Zamar & Arce 1999, González 1999, De Borbón 2005, 2009.…”
Section: Discusión La Identificación De Frankliniella Australis F Gunclassified